Draft Genome Sequence of Daldinia eschscholzii isolated from blood culture - Ng, K.P.; Ngeow, Y.F.; Yew, S.M.; Hassan, H.; Soo-Hoo, T.S.; Na, S.L.; Chan, C.L.; Hoh, C.C.; Lee, K.W.; Yee, W.Y. (2012)
Daldinia eschscholzii is an invasive endophyte that is most commonly found in plant tissues rich in secondary metabolites. We report the draft genome sequence of D. eschscholzii isolated from blood culture. The draft genome is 35,494,957 bp in length, with 42,898,665 reads, 61,449 contigs, and a G+C content of 46.8. The genome was found to contain a high abundance of genes associated with plant cell wall degradation enzymes, mycotoxin production, and antifungal drug resistance.